THE ROLE OF PSYCHOLOGICAL CAPITAL AND JOB RESOURCES ON WORK ENGAGEMENT AMONG GENERATION Z EMPLOYEES - Natalia, Frinsca; Zamralita, Zamralita; Lie, Daniel (Biopsikososial: Jurnal Ilmiah Psikologi Fakultas Psikologi Universitas Mercubuana Jakarta, 2024)
This study aimed to examine the role of psychological capital and job resources on work engagement among Generation Z employees. The number of samples in this study was 137 Generation Z employees at one of the companies dominated by Generation Z employees. This research used a non-experiment quantitative approach by using the Utrecht Work Engagement Scale, Psychological Capital Questionnaire, and Job Demands-Resources Questionnaire. Data were analyzed using simple linear regression. The results showed that psychological capital and job resources had a positive significant effect on work engagement. In this research, it is known that the psychological capital dimension that had the biggest impact on the work engagement of Generation Z employees is resilience. This research also found that the job resources dimension that had the biggest impact on the work engagement of Generation Z employees is feedback This study implied that psychological capital and job resources are two important tools to increase work engagement among Generation Z employees.